To Comply or Not to Comply: Understanding the Discretion in Reporting Public Float and SEC Regulations - Gao, Feng (Contemporary Accounting Research, 2016)
Abstract This paper documents how firms exercise discretion in defining affiliates and reporting public float in response to Securities and Exchange Commission regulations. I find that firms with higher expected compliance costs under section 404 of the Sarbanes‐Oxley Act of 2002 tend to classify more shares as affiliated and report lower public float. In contrast, firms issuing seasoned equity are less likely to underreport public float, possibly due to favorable regulatory treatment for large issuers. These incentives are weakened when future regulatory changes render float less important.